Establishment and Clinical Application of a RPA-LFS Assay for Detection of Capsulated and Non-Capsulated Haemophilus influenzae - Yan Wang; Aibo Liu; Mei Fu; Jingjing Guo; Lei Wang; Xiaohua Zuo; Fenfen Ma (Frontiers in Cellular and Infection Microbiology, 2022)
A recombinase polymerase amplification-lateral flow strip assay was established for detection of the outer membrane protein P6 (omp6) and the capsule encoding gene bexA of Haemophilus influenzae and the detection limit, sensitivity, and specificity were determined. Specific primers and probes were designed based on the published nucleotide sequences of omp6 and bexA. The minimum detection limit was determined with standard strains and the practical applicability of the RPA-LFS assay was assessed by detection of 209 clinical samples. The results confirmed that the RPA-LFS assay was both specific and sensitive for the detection of capsulated and non-capsulated H. influenzae with a detection limit of 1 CFU/µL. The detection rate of the 209 clinical samples was 97.1%, while the detection rate of capsulated H. influenzae was 63.2%. The detection results were consistent with the traditional culture method and dual polymerase chain reaction (PCR), confirming the applicability of the RPA-LFS assay.